Efisiensi dan Efektivitas biaya Rumah Tangga Di Tengah Pandemi Covid-19 Pada kelurahan Tapparan - Mince Batara; Grace S. Mengga; Ade Lisa Matasik; Randi Tangdialla; Stefani Marina Palimbong (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
In the midst of the corona virus disease pandemic that is still sweeping across the world, the impact of the spread of this virus has forced humans to make enormous changes, as well as the people of the Tapparan village. One of the changes that humans must make immediately and cannot be delayed, namely changes in the economy and meeting needs. Humans are required to be more creative in order to be able to survive financially. One way that can be done in order to be able to maintain the financial health of each community is managing household or personal finances. One way of good financial management is cost effectiveness and efficiency. Therefore, it is necessary to conduct training on how to implement Efficiency and Effectiveness of Household Costs in the Middle of the Covid-19 Pandemic in Tapparan Village through (Economically Valued Use of Home Yard Land).